Media Pembelajaran Kotak Kartu Misterius Dalam Keaktifan Siswa - Dhaniar Rafida; Desy Safitri; Saipiatuddin Saipiatuddin (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
This research aims to determine learning outcomes and student activity. With the learning media Kokami (Mysterious Card Box) it can attract students' interest in participating in the learning process and instill knowledge in students. With Kokami media, students can learn and play at the same time, learn about the material being taught so that the lessons make an impression. The method used in this research is classroom action research (PTK). According to Kemmis and Taggart (1988), action research is a form of self-reflective research carried out by participants in social situations (including education) to improve their own practices. This research has determined the target that will be studied to determine the increase in learning outcomes using the Kokami (Mysterious Card Box) learning media, namely for class VIII.4 students at SMP Negeri 172 Jakarta, totaling 35 students consisting of 17 male students and 18 female students. Kokami (Mysterious Card Box) can improve student learning outcomes with student learning outcomes in cycle 1 amounting to 69% with an average learning score of 79 then increasing in cycle 2 by 83% with an average learning outcome score of 83.